Examining the Experiences of Smallholder farmers in Malawi towards Farm Input Subsidies - Tambala, Henry (Department of Social Development, 2023)
The author of this dissertation is the last born in their family. He was born and grew up in the rural area of the Blantyre district of the beloved country Malawi which is also popularly known as the warm heart of Africa for its friendly people. Our African belief states that one's strength is made manifest by the number of children. Like arrows in the pouch of a hunter, so are one's children. They will be able to defend him when his strength is gone in his old age. That led families to have many children even though there were not enough resources for their sustenance and upkeep. Our community consists of agrarian community. When growing up, we prepared our fields between August and September in readiness for the next planting season. Afterward, we could eagerly wait to hear the heavenly voice of thunder and rumblings that announced the coming of the first rains marking the beginning of the new agricultural season. One could catch the distinct earthy flavor of the smell of rain from miles away when rain falls after a long dry spell of weather, and soon, everything would come alive. The land which had been dry, dusty, and barren would turn to beautiful fields covered in green vegetation. Birds could sing beautifully, and livestock could graze as they lazily chased away flies on their backs by the use of their tails. That was usually between October and November, and soon after planting our seeds which maize is a king of all crops, we could count days before enjoying the first fruits of our labors. Those were days when rainfall patterns were predictable and the harvest sure. Close to our village, there was a river that flowed throughout the year. That was where we got water for all our domestic purposes. It was called the Ntengera River, and that means the river that carries all sorts of things. They say that water is life. This river brought all manner of life-giving resources for us. When it flooded during the rainy seasons, it could bring us all sorts of things such as sugarcane and other crops uprooted elsewhere from upstream. It also provided us with delicious chambo and other different varieties of fish. At times, we could go fishing when nsima (mealie pap) was about to be cooked, and within a few minutes, we could come back home with a good catch of fish. Sometimes, we could put poisonous plants into the river to contaminate its waters. That could poison fish and make them grasp in need of fresh air, and in that way, we could easily catch them. It is in this river where we also learned how to swim and play water sports games. When the harvesting period was over, we used to plant vegetables along this river for both home consumption and sale in the urban sector of Blantyre. We could apply pesticides such as Dichlorodiphenyltrichloroethane (DDT) to prevent pests from attacking our crops to enhance vegetable production. No one could pronounce this name in our village, and everybody opted for its abbreviation. The pesticide is a general name that refers to a wide range of other compounds aimed at promoting crop productivity and regulating other unwanted herbs, fungi, insects, rodents, molasses, and many other pests. Ideally, the intention was to kill pests and leave the crops uncontaminated. However, with pesticides such as DDT, this has not always been the case. Such pesticides targeted other organisms such as insects and other invertebrates. Organisms such as insects and earthworms act as agents of cross-pollination and natural recyclers for the soil ecosystem. No wonder that some of our arable lands are no longer productive as they used to be. Even though the banning of DDT pesticides from using it happened as early as the 1960s in the developed world, most developing nations continued to use them due to a lack of alternatives. Eventually, these pesticides have found their way into the environment and human bodies with devastating impacts. Our late grandfather used to tell us that some chronic diseases affecting people nowadays were unheard of during their youthful days. In search of more land for cultivation and better access to water sources, we used to cultivate close to the river banks, and sometimes we went as far as clearing off plants and vegetation that grew along the river banks. For us, there was nothing wrong with that. Everyone was doing it. Little did we know that with all these Anthropocene practices, we were squeezing the life out of our beloved river and fast-pacing it to dry up. The more we stripped off the dressing for that river, the more it became naked and thus vulnerable to direct tropical sunshine. Trees and vegetation are part of the water cycle and, without their presence, leave the water cycle with some gaps. This river that used to flow throughout the year has become a seasonal river with waters flowing through it only during the rainy season. Topsoil washed away from upstream has now filled up natural water reservoirs. That makes the rainwater rush through the Ntengera river on its way to the Shire River and then disappears into the mighty Zambezi river. The concentration of washed-up nutrients has not only helped to contaminate the water quality, but it has also raised fecal coliforms and other sediment loads that have promoted the damage of aquatic ecosystems. Is this the sixth mass extinction after the fifth extinction of dinosaurs? Can environmental pollution be reversed? Can there be restoration or repair of the broken water cycle for that beloved Ntengera river and all other water bodies and the entire ecosystems? Can we travel back to the future through our actions to make right what went wrong? What about the disrupted livelihoods of the rural communities now displaced from their original places of habitation in search of better livelihoods? The disruption of their rural economies was due to anthropogenic environmental changes of modern globalization practices? This study is a story of those changes—stories of how the landscape and the environment have changed. These are stories of change that have ended up transforming non-human and humans in our community and our neighbours and their neighbours to a national, regional, and continental level. That is an ethnographic story of rural communities both for humans and nonhumans. It is a story about the supremacy of human beings over nature and the ecological trap that humanity has set for itself and the entire ecosystem. It is a story of rural communities whose livelihoods have been disturbed by rich developed nations and how they continue to exploit local people and extract their only last resource and means of livelihood - subsistence farming through agricultural intensification and promotion of new technology.